2013
DOI: 10.4028/www.scientific.net/kem.543.515
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Immunosensors for Toxins' Detection in Foodstuffs

Abstract: The procedures of detecting trace concentrations of okadaic acid and staphylococcal enterotoxin A in foodstuffs by the piezoelectric immunosensors have been developed. The conditions for immobilizing antibodies to toxins on the surface of the sensors gold electrode have been facilitated. The calibration curves for the detection of okadaic acid and staphylococcal enterotoxin A are linear in the range of concentrations 5500 ng·ml-1 and 1-80 ng·ml-1, the limits of detection are 1.4 and 0.4 ng·ml-1 correspondingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The same authors later demonstrated applicability to contaminated milk samples . Others have used a similar piezoelectric immunosensor based on monoclonal antibodies to detect SEA in chicken meat and milk with improvements to sensitivity (0.4 ng/mL) …”
Section: Physical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors later demonstrated applicability to contaminated milk samples . Others have used a similar piezoelectric immunosensor based on monoclonal antibodies to detect SEA in chicken meat and milk with improvements to sensitivity (0.4 ng/mL) …”
Section: Physical Techniquesmentioning
confidence: 99%
“…1011 Others have used a similar piezoelectric immunosensor based on monoclonal antibodies to detect SEA in chicken meat and milk with improvements to sensitivity (0.4 ng/mL). 1012 Cantilever devices are also capable of multiplexed and sensitive detection with minimal sample waste and usage time. Microcantilever sensors can similarly respond to surface stress changes produced by a biorecognition event.…”
Section: ■ Spectroscopic Sensorsmentioning
confidence: 99%